Food security implications of rice value chain management in Bangladesh - Mujeri, Mustafa K.; Ahmed, Nazneen; Hossain, M. I. (University Press Limited, 2021)
Since Bangladesh’s independence in 1971, the country’s population has more than doubled to over 160 million in 2016. Despite a large population and severe resource constraints, the country has achieved significant development including steady growth in per capita income and impressive gains in human development. The incidence of poverty has also declined from nearly 60 percent in the early 1990s to less than a quarter in recent years. However, there are still millions of people who are food insecure, as commonly understood, in terms of complex multi-faceted issues concerning not just agriculture, technology and trade, but also involving multiple social and ecological considerations.